Sosialisasi Penggunaan Media Sosial Untuk Meningkatkan Kinerja E-Government di Kecamatan Mlati Kabupaten Sleman Yogyakarta - Amir Hamzah; Muhammad Sholeh; Uning (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
The use of information technology to support E-government has long been proclaimed by the Government. However, implementation at the sub-district and village levels still faces many obstacles. Based on a field study in Mlati District, it was found that the obstacles were a lack of awareness and technical ability of media managers. The purpose of this service is to increase awareness and ability of official media managers at the sub-district and village levels so that the communication of government programs is better. The targets of this activity are media managers from representatives of the Community Information Group (KIM), village representatives and Information Management and Documentation Officers (PPID) in Mlati District. The method used is lectures and assistance in the use of social media for disseminating government program information. Evaluation of activities is carried out with post-activity questionnaires to participants. The evaluation results show that 86% of participants are satisfied and 90% get additional knowledge in managing official social media of sub-district and village governments